MICROSCOPICAL OBSERVATIONS ON CISSUS VITIGINEA L. - Pratap, G. Penchala; Sudarsanam, G.; Prasad, G. P.; Sekhar, J. (International Journal of Ayurveda and Pharma Research, 2015)
The present study discloses detailed investigation on Macro and Microscopical characters of the leaves and roots of Cissus vitiginea L. Yanadhi tribes of Nellore district, have been using the root powder and leaf paste of C. vitiginea as a single drugs remedy to heal the wounds and to get immediate relief from swellings and sprains respectively. The plant belongs to Vitaceae family. In dried form identification of leaves and roots is hard and at present authentic pharmacognostical data is not available. With this view, leaves and roots of C. vitiginea were subjected to various pharmacognostical studies like, powder microscopy, sectioning, maceration and florasense studies to identify authentically. In the microscopical studies, different cell structures like trichomes, elongated fibers, raphide sacs, acicular crystals and different arrangements like, raphide sacs in the parenchymatous region reddish tannin content in the phloem region were noticed.